Green Economy Dalam Mengembangkan Jiwa Green Entrepreneurship Siswa Sekolah Dasar - Arfi Purnama Nur Indah; Irawati Nuraeni; Tin Rustini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Social Sciences (IPS) is a science related to the social environment and a branch of science that studies human behavior as members of society. Social studies is studied at primary education, secondary education, and even tertiary level. In social studies, history, geography, sociology, economics, and so on are studied. In economics, there is discussion about the green economy. Green economy is an economic idea that aims to improve welfare and social equality, while reducing the risk of environmental damage. This research aims to analyze how a green economy can develop the spirit of green entrepreneurship, especially in elementary school students. This research uses qualitative methods and the data collection technique uses library research by collecting data sourced from books, journals or literature that discuss the problems discussed.